Local action of moderate heating and illumination induces propagation of hyperpolarization electrical signals in wheat plants - Yudina, Lyubov; Sukhova, Ekaterina; Popova, Alyona; Zolin, Yuriy; Abasheva, Karina; Grebneva, Kseniya; Sukhov, Vladimir (Frontiers in Sustainable Food Systems, 2023)
Electrical signals (ESs), which are generated in irritated zones of plants and propagate into their non-irritated parts, are hypothesized to be an important mechanism of a plant systemic response on the local action of adverse factors. This hypothesis is supported by influence of ESs on numerous physiological processes including expression of defense genes, production of stress phytohormones, changes in photosynthetic processes and transpiration, stimulation of respiration and others. However, there are several questions, which require solution to support the hypothesis. Particularly, the non-physiological stimuli (e.g., strong heating or burning) are often used for induction of ESs; in contrast, the ES induction under action of physiological stressors with moderate intensities requires additional investigations. Influence of long-term environmental factors on generation and propagation of ESs is also weakly investigated. In the current work, we investigated ESs induced by local action of the moderate heating and illumination in wheat plants under irrigated and drought conditions. It was shown that combination of the moderate heating (40°C) and illumination (blue light, 540 µmol m-2s-1) induced electrical signals which were mainly depolarization electrical signals near the irritation zone and hyperpolarization electrical signals (HESs) on the distance from this zone. The moderate soil drought did not influence HESs; in contrast, the strong soil drought significantly decreased amplitude of HESs. Finally, it was shown that the moderate heating could induce HESs without additional action of illumination. It was hypothesized that both hyperpolarization and depolarization ESs could be caused by the hydraulic wave.